Disruption of lipid raft microdomains, regulation of CD38, TP53, and MYC signaling, and induction of apoptosis by lomitapide in multiple myeloma cells - Saeed, Mohamed; Boulos, Joelle; Mücklich, Sabrina B.; Leich-Zbat, Ellen; Chatterjee, Manik; Klauck, Sabine; Efferth, Thomas (Cancer genomics & proteomics, 2022)
Background/Aim: Multiple myeloma (MM) is characterized by accumulation of a malignant clone of plasma cells in the bone marrow. Curative treatments are not yet available. Therefore, we undertook a drug repurposing approach to identify possible candidates from a chemical library of 1,230 FDA-approved drugs by virtual drug screening. As a target, we have chosen the non-receptor Bruton’s tyrosine kinase (BTK) which is one of the main regulators of the MM biomarker CD38. Materials and Methods: In silico virtual screening was performed by using PyRx. Flow cytometry was applied for cell cycle and apoptosis analysis. Furthermore, protein and gene expression was determined by western blotting and microarray hybridization. Lipid raft staining was observed by confocal microscopy. Results: The in silico identified lipid-lowering lomitapide presented with the strongest cytotoxicity among the top 10 drug candidates. This drug arrested the cell cycle in the G2/M phase and induced apoptosis in MM cells. Western blot analyses revealed that treatment with lomitapide induced cleavage of the apoptosis regulator PARP and reduced the expression of CD38, an integral part of lipid rafts. Using confocal microscopy, we further observed that lipid raft microdomain formation in MM cells was inhibited by lomitapide. In four MM cell lines (KMS-12-BM, NCI-H929, RPMI-8226, and MOLP-8) treated with lomitapide, microarray analyses showed not only that the expression of CD38 and BTK was down-regulated, but also that the tumor suppressor gene TP53 and the oncogene c-MYC were among the top deregulated genes. Further analysis of these data by Ingenuity pathway analysis (IPA) suggested that lomitapide interferes with the cross-talk of CD38 and BTK and apoptosis-regulating genes via TP53 and c-MYC. Conclusion: Lomitapide treatment led to disruption of lipid raft domains and induction of pro-apoptotic factors and might, therefore, be considered as a potential therapeutic agent in MM.